PENGEMBANGAN MEDIA FRACTION MATH PADA MATA PELAJARAN MATEMATIKA MATERI PECAHAN KELAS V SD - Ganda Agus Setiawan; Endang Wahju Andjariani; Galuh Kartika Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Anything that can be used to communicate messages or information during the teaching and learning process is called learning media. Teaching math, especially on fraction material, will be easier if you use learning media. The learning methods used by teachers are still in the form of lectures and assignments, so that students still do not understand fraction material. Based on this, the researcher thought it was necessary to use Fraction Math learning media in order to determine the students' response to the media, and to find out the difference in pretest and posttest results. The author uses research and development (R&D) as a research methodology. This research and development approach is based on the Borg and Gall development model, which was altered from Sugiyono  The research was conducted on fifth grade stundents of SDN Gempolsari Tanggulangin with a total of 33 students. The results showed 84.8% of students understood the fraction material better after using Fraction Math media, it’s indicating that Fraction Math media is suitable for use. Class V students of SDN Gempolsari Tanggulangin showes a positive respones to the use of Fraction Math media and this media was provend to be able to improve learning outcomes achieved with a satisfaction score of 88.60 (strongly agree).